Proving Peaceful Islam through the Application of Al-'Illat Wa Al-Ma'lûl Approach in Reading Qur’anic Verses of War (Interpretation of Q.2: 190-194 and Q.9: 5-15) - Iftitah Jafar; Mudzhira Nur Amrullah (Sunan Kalijaga: International Journal of Islamic Civilization, 2019)
This paper will prove Islam as a religion of peace by using al-illat wa al-ma'lûl approach in reading Qur’anic verses of war. Qur’anic verses of war have been a crucial problem in interfaith relation. Non-Muslims used such verses as a weapon to label Islam as a violent religion. Moreover, some terrorists justified their violent action with verses of war. However, Muslims insist that such verses basically do not express violence especially if they are properly understood. Radical understanding of Qur’anic texts is partly caused by the approach that exegetes use. Apart from the approach is the use of literal translation and atomistic approach. Atomistic approach suggests the readers to split a verse and treat it separately without relating it to other parts of the verse. Moreover, it does not pay a specific attention to the historical context of the texts (asbȃb al-nuzȗl). In addition, it neglects the correlation of the verses (munᾱsaba). Some approaches have contributed to the problem includes: 1. System approach, 2. Esoteric interpretation approach, and 3. Historic-contextual approach. However, these three approaches did not solve the problem. Therefore, the writer introduces al-illat wa al-ma'lûl approach. The research question is how to prove Islam as a religion of peace by implementing al-‘illat wa al-ma‘lȗl approach in understanding Qur’anic verses of war? Methodologically, this approach was adopted from the concept of cause and effect in various studies, specifically: Physics, History, Philosophy, Communication as well as Islamic studies, especially: Uṣȗl al-Fiqh, Ḥadȋth and Tafsȋr. The approach runs through 4 steps: 1. Literal analysis of key words, especially "qᾱtil," in Q.2:190-194 and Q.9:5-15. 2. Analyzing macro context of revelation (asbȃb al-nuzȗl al-‘ȃmm) and the micro context of the texts (asbȃb al-nuzȗl al-khȃṣs). 3. Analyzing the correlation of the verse internally and externally. 4. Determine which part of the verse is the cause (al-‘illat) and which one is the effect (al-ma‘lûl). It also determines which verses function as a cause and which ones function as an effect. The result of study shows that: 1. The order to fight unbelievers has been preceded by a cause that unbelievers have declared war. 3. The order to fight idolaters wherever they found them is issued when the war is raging and in certain places and in certain time. 4. The command to fight is upright on a noble purpose namely justice, liberation and self-defense. This command to fight is based on the real condition of Muslims whom were oppressed, persecuted, tortured and expelled. This war is also upright on the ethics of war, such as not killing old men, women and children, not destroying houses of worship, and plantations. To conclude, all command to fight for Muslim is a consequence of the previous events as a cause. Therefore, Islam is a peaceful religion it is a defensive and not aggressive or offensive religion.